Periodontal Disease in the COVID-19 Era: Potential Reservoir and Increased Risk for SARS-CoV-2 - Martinna Bertolini; Afroditi Pita; Sungeun Koo; Anibal Cardenas; Archana Meethil (Association of Support to Oral Health Research (APESB), 2022)
Since December 2019, an outbreak of Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in China and is now becoming a global Pandemic, with over 10.5 million cases worldwide. Angiotensin-converting enzyme-2 (ACE-2) has been considered the main receptor for the SARS-CoV-2 entry into human cells, and they are known to be present not only in lungs (therefore the common viral pneumonia) but also in nasopharyngeal mucosa, salivary cells and oral epithelial cells. Moreover, there seems to be recent evidence showing that the crevicular fluid on the periodontal pockets of patients presenting periodontitis could harbor SARS-CoV-2 and act as a potential reservoir for increased viral load in the oral cavity of COVID-positive patients. Additionally, sites with active periodontal disease might contribute for virus binding and tissue infection due to elevated expression of furin and cathepsin L proteases, which play a major role in enabling the SARS-CoV-2 to bind ACE-2 receptors and facilitating endosomal fusion in the host cells. Taken together this news and views article highlight possible virus reservoirs in COVID-positive patients, as well as increased risk for infection in patients with active periodontal disease, further proposing potential targets for antiviral intervention on SARS-CoV-2 infection.